2019
DOI: 10.3390/biom9120849
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Induce Strong, Dose-Dependent Inhibition of Etiolated Pea Seedling Growth Correlated with Ethylene Production

Abstract: We have recently discovered that brassinosteroids (BRs) can inhibit the growth of etiolated pea seedlings dose-dependently in a similar manner to the ‘triple response’ induced by ethylene. We demonstrate here that the growth inhibition of etiolated pea shoots strongly correlates with increases in ethylene production, which also responds dose-dependently to applied BRs. We assessed the biological activities of two natural BRs on pea seedlings, which are excellent material as they grow rapidly, and respond both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Suppression of plant growth is a result of mitosis blocking, DNA replication inhibition, the breakdown of cell integrity and cell membrane, and the degradation of cell wall polysaccharides induced by high doses of BRs [ 36 , 37 , 38 , 39 ]. Jiroutova et al [ 40 ] showed that high EBL concentration (above 0.5 µM) considerably enhanced ethylene production, which induces plant senescence. Furthermore, high doses of BRs cause gibberellin inactivation, which is correlated with the inhibition of rice ( Oryza sativa ) cell elongation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of plant growth is a result of mitosis blocking, DNA replication inhibition, the breakdown of cell integrity and cell membrane, and the degradation of cell wall polysaccharides induced by high doses of BRs [ 36 , 37 , 38 , 39 ]. Jiroutova et al [ 40 ] showed that high EBL concentration (above 0.5 µM) considerably enhanced ethylene production, which induces plant senescence. Furthermore, high doses of BRs cause gibberellin inactivation, which is correlated with the inhibition of rice ( Oryza sativa ) cell elongation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jiroutová et al also found that BRs inhibited the growth of Pisum sativum L. seedings, along with a reduction in stem elongation rate, an increase in lateral expansion, and an exaggeration of the apical hook curvature. Subsequently, they demonstrated that BRs promoted the biosynthesis of endogenous ethylene, and the inhibitory effect of BRs was mediated by ethylene [ 19 ]. In addition, it was found that, compared with wild-type fruit, a higher ethylene content was obtained in the SlCYP90B3 -OE fruit [the transgenic lines overexpressing SlCYP90B3 (a BR transcription factor) of Solanum lycopersicum ].…”
Section: Brassinosteroids and Ethylenementioning
confidence: 99%
“…In recent years, an increasing number of SMC types have been indicated to interact with BRs. For example, BRs have been shown to interact with some typical small molecules such as NO, ethylene, hydrogen peroxide (H 2 O 2 ), and H 2 S to modulate plant growth and tolerance to stress stimulus [ 18 , 19 , 20 , 21 ]. This provides further insight into the function mechanism of SMCs and a new type of plant hormones in plant growth and development processes.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of BR pathways could also result in altered growth phenotypes, since they regulate elongation growth and cell expansion as auxins [43,44], but to our knowledge, there was no connection yet made so far with auxinic herbicides. However, there is an observation that BR can inhibit the growth of etiolated pea seedlings by increasing ethylene production, and this effect is stronger than the one after IAA treatment [45]. Such experiments suggest that also the induction of BR biosynthesis (Figure S6A) by auxinic herbicide treatment could contribute to the increased ethylene production, as was estimated by the high ACC levels that were found (Figure 5).…”
Section: Molecular Phenotype Of B Napus Treated With Auxinic Herbicidesmentioning
confidence: 79%